Branding Strategy Based on 5M Management in Improving the Existence and Competitiveness of Islamic Education Institutions - Muhammad Sahlan; Muhammad Ilzamul Khoir (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
This study aims to identify the challenges faced by Madrasah Aliyah Nurul Jadid in increasing public trust by using the 5M method as an image management strategy. This study uses a qualitative case study approach to understand how internal and external factors build public trust in the madrasah. The research findings show that internal challenges include improving Human Resources (HR), applicable systems, marketing strategies, and providing supporting facilities. Meanwhile, external challenges are related to the readiness of the community to understand and adapt to the system implemented in the madrasah. It is necessary to implement 5M-based image management, which includes Man (human), Method (method), Material (resources), Money (funding), and Media (communication tools). The results of this study provide an in-depth understanding of the strategy for building public trust contextually based on the social and cultural conditions of Madrasah Aliyah Nurul Jadid. These findings can be a reference for further research to strengthen the concept of image management in various educational institutions.